Penerapan Kode Etik dalam Membentuk Mahasiswa yang Berkarakter dan Berprestasi - Deyan Damar Aji (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
In the midst of increasingly advanced developments, student ethics are increasingly declining. One of the responsibilities of higher education is to produce students with character and achievements. Therefore, this research aims to examine the implementation of the student code of ethics and its impact in creating students with character and achievements. This research aims to determine the process of implementing the code of ethics and its impact on students. The method used in this research is descriptive qualitative. The research results show that the implementation of the student code of ethics has gone well and has had a positive impact in forming students with character and achievements by 70.71%. From the results of implementing the code of ethics, students show their individual character and achievements which are evaluated based on aspects of student character and aspects of outstanding students. In implementing the code of ethics, there are supporting and inhibiting factors.